Comprehensive Obstetric Care for Mrs. F.D at The Dumbo Raya Health Center, Gorontalo City - Alza, Nurfaizah; Mohamad, Selvi; Yulianingsih, Endah; Ibrahim, Fatmawati; Abdul, Salsabila Putri Aprilda (Jurnal Midwifery, 2025)
Introduction Maternal Mortality Rate (MMR) and Infant Mortality Rate (AKB) are still national health problems. Based on data from the Dumbo Raya Health Center in 2022–2024, there was an increase in AKI cases from 0 to 2 cases, and AKB from 5 to 11 cases, caused by IUFD, congenital disorders, diarrhea, and leaky heart. Comprehensive obstetric care aims to provide continuous services from pregnancy to birth control. Method This research method uses a descriptive method through a case study approach. The subject used in this study was Mrs. F.D, aged 24 years, who was accompanied from 30 weeks of gestation. Results During pregnancy, mothers complain of back pain and frequent urination, which is successfully overcome through education, light massage, warm compresses, and changes in fluid consumption patterns. Labor takes place through sectio caesarea due to macrosomy indications. During the postpartum period, SC wound monitoring, uterine involution, lochea, breastfeeding education, personal hygiene, and family planning counseling are carried out. The mother chooses to use MAL contraceptives and plans to use an IUD. Neonatal visits are carried out three times, the baby is in normal condition. Conclusion The results of care from pregnancy to postpartum show that services take place optimally, characterized by the absence of complications. This comprehensive midwifery care is expected to increase maternal awareness in implementing good health practices and support maternal and infant health as a whole and sustainable.